Endometriosis presenting as carcinoma colon in a perimenopausal woman - Tanuja Muthyala; Pooja Sikka; Neelam Aggarwal; Vanita Suri; Rajesh Gupta; Uma Nahar (Wolters Kluwer Medknow Publications, 2015)
Endometriosis is a common benign disease of reproductive age women, and can involve the intestinal tract. Inconsistent clinical presentation, similar features on radiological imaging and colonoscopy with other inflammatory and malignant lesions of the bowel makes the preoperative diagnosis of bowel endometriosis difficult. We present a case of a 42-year-old perimenopausal female clinically presented, investigated and managed in the lines of carcinoma of sigmoid colon. She underwent terminal ileac resection with end to end anastomoses, Hartmann's procedure and total hysterectomy with bilateral salpingoophorectomy. The histopathological report revealed endometriosis of small intestine, large intestine, mesentery, right ovary and adenomyoma of uterus. Thus, bowel endometriosis should also be considered as differential diagnosis in reproductive age women with gastrointestinal symptoms or intestinal mass of uncertain diagnosis.